Design and implementation of the driver system for Hamamatsu C12880MA microspectrometer - Sokołowski, Patryk; Wróbel, Maciej Stefan; Karpienko, Katarzyna (Photonics Letters of Poland, 2021)
Recent miniaturization developments in devices for spectroscopy have reduced greatly their costs and increased their availability for a wide range of users and applications. This paper presents the design and implementation of a driver system for a Hamamatsu C12880MA microspectrometer. The system implementation was carried out and compared using two independent microcontroller modules: Arduino Uno and STM32F411RE Nucleo. We assessed the microspectrometer system parameters like resolution and integration time, as influenced by the choice of a driver microcontroller. We present a possible application of this microspectrometer system for measurements of ground coffee beans reflectance for control of coffee roasting. Full Text: PDF References Crocombe RA. Portable Spectroscopy. "Portable Spectroscopy", Applied Spectroscopy. 2018;72(12):1701-1751 CrossRef Datasheet Hamamastu C12880MA DirectLink Datasheet Arduino Uno DirectLink Datasheet STM32F411RE DirectLink Hernández, J. A., B. Heyd, and G. Trystram. "Prediction of brightness and surface area kinetics during coffee roasting." Journal of Food Engineering 89.2 (2008): 156-163. CrossRef